Extensive molecular and clinical heterogeneity in patients with histologically diagnosed cns-pnet treated as a single entity: a report from the children’s oncology group randomized ACNS0332 trial - Hwang, Eugene; Kool, Marcel; Capper, David; Chavez, Lukas; Deimling, Andreas von; Jones, David T. W.; Pfister, Stefan; Brabetz, Sebastian (Journal of clinical oncology, 2018)
Children with histologically diagnosed high-risk medulloblastoma, supratentorial primitive neuroectodermal tumor of the CNS (CNS-PNET), and pineoblastoma (PBL) have had poor survival despite intensive treatment. We included these patients in this Children’s Oncology Group trial. Molecular profiling later revealed tumor heterogeneity that was not detectable at protocol inception. Enrollment of patients with CNS-PNET/PBL was subsequently discontinued, and outcomes for this part of the study are reported here.